Role of informal healthcare providers in tuberculosis care in low- and middle-income countries: A systematic scoping review. - Poshan Thapa; Rohan Jayasuriya; John J Hall; Kristen Beek; Parthasarathi Mukherjee; Nachiket Gudi; Padmanesan Narasimhan (PLoS ONE, 2021)
Achieving targets set in the End TB Strategy is still a distant goal for many Low- and Middle-Income Countries (LMICs). The importance of strengthening public-private partnership by engaging all identified providers in Tuberculosis (TB) care has long been advocated in global TB policies and strategies. However, Informal Healthcare Providers (IPs) are not yet prioritised and engaged in National Tuberculosis Programs (NTPs) globally. There exists a substantial body of evidence that confirms an important contribution of IPs in TB care. A systematic understanding of their role is necessary to ascertain their potential in improving TB care in LMICs. The purpose of this review is to scope the role of IPs in TB care. The scoping review was guided by a framework developed by the Joanna Briggs Institute. An electronic search of literature was conducted in MEDLINE, EMBASE, SCOPUS, Global Health, CINAHL, and Web of Science. Of a total 5234 records identified and retrieved, 92 full-text articles were screened, of which 13 were included in the final review. An increasing trend was observed in publication over time, with most published between 2010-2019. In 60% of the articles, NTPs were mentioned as a collaborator in the study. For detection and diagnosis, IPs were primarily involved in identifying and referring patients. Administering DOT (Directly Observed Treatment) to the patient was the major task assigned to IPs for treatment and support. There is a paucity of evidence on prevention, as only one study involved IPs to perform this role. Traditional health providers were the most commonly featured, but there was not much variation in the role by provider type. All studies reported a positive role of IPs in improving TB care outcomes. This review demonstrates that IPs can be successfully engaged in various roles in TB care with appropriate support and training. Their contribution can support countries to achieve their national and global targets if prioritized in National TB Programs.